THEME: CREATING LEARNER-CENTERED TEACHING. A SCIENTIFIC APPROACHES TO ENHANCING EDUCATIONAL OUTCOMES - Eshboyev Abdushukur Berdinazarovich (TADQIQOTLAR, 2025)
Abstract Learner-centered teaching (LCT) has emerged as a transformative approach in education  that  prioritizes  the  needs,  interests,  abilities,  and  active  involvement  of students  in  the  learning  process.  This  scientific  article  explores  the  theoretical foundations, principles, practical strategies, and challenges involved in implementing learner-centered  teaching  across  diverse  educational  settings.  Drawing  upon constructivist learning theories, cognitive psychology, and pedagogical research, the study  emphasizes  the  shift  from  traditional  teacher-directed  methods  to  student-empowered  learning  environments.  The  article  concludes  by  offering recommendations  for  educators,  institutions,  and  policymakers  aiming  to  foster effective learner-centered practices.